Pre-harvest desiccation of soybean intercropped with Brachiaria brizantha under reduced doses of graminicide - Silva, Andréia Cristina da; Freitas, Francisco Cláudio; Ferreira, Lino Roberto; Freitas, Rogério Soares (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effects of pre-harvest desiccation of soybean and Brachiaria brizantha cv. Marandu, treated with reduced doses of graminicide under intercropping system on soybean mechanical harvest as well as forage regrowth and straw yield. A 5x3 factorial scheme was used, consisting of five rates of fluazifop-p-butyl (0, 15, 30, 45 and 60 g ha-1) and three intercropping desiccation managements, without desiccation or desiccated at R7 or R8 soybean stage, in a randomized complete block, with four replications. Two control treatments were included; soybean and B. brizantha under monocrop kept clean by hand hoeing. B. brizantha was highly susceptible to herbicide. Soybean and B. brizantha intercropped at 15 g ha-1 of graminicide and desiccated at R7 soybean stage allowed soybean mechanical harvest and grain yield similar to those achieved under monocrop, providing dry mass accumulation of B. brizantha of 4.6 t ha-1, 60 days after soybean harvest. B. brizantha intercropped with soybean, without graminicide application, accumulated 6 t ha-1 of dry mass at soybean harvest and 9.3 t ha-1, 60 days after, with mass accumulation of B. brizantha under monocrop being 13.3 and 21.6 t ha-1, respectively.